The Charter of the Kanak People: in pursuit of "cooperative and balanced legal pluralism" in New Caledonia. Issue 3 (1st September 2016) - Dickins Morrison, Rowena
ABSTRACT: In April 2014, a significant number of New Caledonia's Kanak customary authorities adopted the "Charter of the Kanak People on the Common Foundation of Fundamental Values and Principles of the Kanak Civilisation". The product of a year-long consultation process led by the Customary Senate, the Charter's overall objective is to institute "cooperative and balanced legal pluralism" (Preamble, 11) in an internally decolonised New Caledonia. The Charter asserts the indigenous rights of the Kanak people and aims to transform the plural legal order(s) currently existing in this French Pacific archipelago, in which Kanak "customary law" is notably applied by the state to civil matters between individuals of "customary civil status" and to "customary lands". Adopting a plurality of perspectives on "legal pluralism", this paper analyses the objectives and implications of the Charter in terms of the ways in which it aims to redraw the contours of "legal pluralism" in the country at a foundational and a mechanical level, while allowing for a range of interpretations so as to maximise its potential impact in the context of the upcoming decisions regarding New Caledonia's future political and legal landscape following the conclusion of the Noumea Accord "decolonisation" process.